2008
DOI: 10.1038/leu.2008.336
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of myeloma bone disease

Abstract: Bone disease in multiple myeloma (MM) is characterized by lytic bone lesions, which can cause severe bone pain, pathologic fractures and hypercalcemia. However, the lytic bone disease in MM differs from that in other cancer patients who have lytic bone metastases. Although increased osteoclastic bone destruction is involved in MM and other tumors involving bone, in contrast to other tumors, once the MM tumor burden exceeds 50% in a local area, osteoblast activity is either suppressed or absent.1 The basis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
186
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(188 citation statements)
references
References 77 publications
2
186
0
Order By: Relevance
“…MBD is characterized by a double component of increased OC formation and resorption, whereas OB formation and function are impaired [7, 8]. Although we did not find any significative effect of CXCL1, CXCL5 or CXCL6 on the osteogenic or osteoclastogenic processes (data not shown), we observed that CXCL1 functioned as a chemoattractant for OC precursors (Fig.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…MBD is characterized by a double component of increased OC formation and resorption, whereas OB formation and function are impaired [7, 8]. Although we did not find any significative effect of CXCL1, CXCL5 or CXCL6 on the osteogenic or osteoclastogenic processes (data not shown), we observed that CXCL1 functioned as a chemoattractant for OC precursors (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…These interactions have bidirectional consequences: on the one hand, myeloma cells perturb the BM homeostasis, causing anemia and immune suppression [6]. Further, these interactions may uncouple normal bone remodeling, reducing osteoblast (OB) differentiation and function and promoting osteoclast (OC) formation and resorption, and leading to the development of osteolytic bone lesions [7, 8]. On the other hand, interactions of myeloma cells mostly with BM stromal cells and OCs, activate pleiotropic cascades of proliferative, survival and migration signaling pathways in myeloma cells, and protect them from chemotherapy-induced apoptosis [1, 9].…”
Section: Introductionmentioning
confidence: 99%
“…It may constitute the first sign of the disease in some cases [7,14]. In MM, osteolysis is due to excessive osteoclastogenesis caused by the release of various cytokines by the malignant plasma cells, and osteolysis in turn stimulates MM proliferation (causing the “vicious cycle”) [1,4,15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…It usually happens in the advanced stage of the disease but can be the first sign of MM [7,8]. Bone destruction is due to a stimulated osteoclast activity in the vicinity of plasmacytomas that release several cytokines which stimulate osteoclastogenesis associated with a profound decrease in osteoblast activity leading to uncoupling in bone remodeling [1,9]. Bone remodeling in MM is characterized by a vicious circle in which malignant plasma cells stimulate osteoclasts which in turn stimulate tumor growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation